Educational Supervision to Improve Teachers’ Learning Quality and Performance in the New Normal Era - Dety Mulyanti (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to discuss the role of individual technical academic supervision in improving the quality of learning in the "new normal" era after the COVID-19 pandemic. The research method used is a qualitative descriptive method involving school principals, teachers, and students at Pelita Nusantara Elementary School. The results showed that individual technical academic supervision was carried out by the principal through several stages, including planning supervision by creating programs and instruments using the Google Drive and Google Form applications. Supervision is carried out through online class visits, learning observations, and individual talks with teachers. Digital-based supervision provides efficiency in the supervision process, enabling principals to monitor teacher activities in various classes without time and place restrictions. However, online supervision also has weaknesses related to the lack of direct interaction between supervisors and teachers. Supervision of learning materials is also an important part of academic supervision, where the school principal checks and assesses learning device documents such as lesson plans in accordance with the new curriculum. Recommendations for further research include comparative studies on the effectiveness of various supervision platforms, developing more interactive supervision platforms, in-depth research on the impact of technology on supervision, and exploring the implementation of peer-to-peer supervision.